Maradona y las reglas del juego : una interpretación sociológica de la mano de Dios - Magalhães Brito, Simone; Ventura de Morais, Jorge; Velho Barreto, Túlio (El Colegio de México, 2012)
From a discussion of the Maradona goal known as “the hand of God”, the aim of this paper is to present the theoretical problems of the relationship between rules and moral rules in fi gurational sociology.